European Power and Impoliteness Strategies in This Earth of Mankind - Apriliana, Candra (Journal of Literature, Linguistics, & Cultural Studies, 2022)
This study aimed to investigate the types, functions, and purposes of impoliteness strategies and power used by European characters in This Earth of Mankind novel. This study used a descriptive qualitative research method because the data are in the form of conversation between Europeans and Indigenous people that contain the elements of impoliteness and power contained in the novel. There are four theories used in this research. The first theory belongs to Culpeper (1996) to identify types of impoliteness. The second theory belongs to Culpeper (2011) to identify impoliteness functions. Furthermore, Beebe's (1950) and Bousfield's (2008) theories are used to understand the purpose of using power through impolite language. The first result showed that European characters in the novel use all kinds of impoliteness according to Culpeper (1996). The types of impoliteness used are (1) direct impoliteness (Bald on record impoliteness), (2) positive impoliteness, (3) negative impoliteness, (4) sarcasm or mock politeness, and (5) withhold politeness. From the 40 data, there was negative impoliteness as the most frequently used number with a total of 17 conversations. The second result found two impolite functions, namely affective function with a total of 22 conversations and coercive with a total of 11 conversations. The last result revealed that the purpose are often used by European in This Earth of Mankind novel is to appear as superior with a total of 22 conversations. Then, the least purpose is to reactivate the power with a total of 1 conversation.